2022
DOI: 10.3390/nu14112240
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Treatment Outcomes for Eating Disorders: A Case-Matched, Retrospective Pre–Post Comparison

Abstract: Eating disorders (EDs) are increasingly emerging as a health risk in men, yet men remain underrepresented in ED research, including interventional trials. This underrepresentation of men may have facilitated the development of women-centered ED treatments that result in suboptimal outcomes for men. The present study retrospectively compared pre- vs. post-treatment outcomes between age-, diagnosis-, and length-of-treatment-matched samples of n = 200 men and n = 200 women with Anorexia Nervosa (AN), Bulimia Nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 75 publications
2
13
0
Order By: Relevance
“…Thus far, the reasons for pronounced weight reductions with simultaneous parity in psychopathology outcomes remain elusive, as we cannot exclude that established assessments (like the EDE‐Q) may be less sensitive towards capturing men‐specific psychopathology. As argued elsewhere (Halbeisen, Braks, et al., 2022), men may show pronounced weight reductions due to higher levels of energy expenditure (Redman et al., 2014), but increased weight reductions could also reflect differences in therapy adherence between men and women. Given the paucity of studies on gender differences in EDs, especially for treatment outcomes in BED, further substantiation of these observations and their long‐term consequences is needed.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Thus far, the reasons for pronounced weight reductions with simultaneous parity in psychopathology outcomes remain elusive, as we cannot exclude that established assessments (like the EDE‐Q) may be less sensitive towards capturing men‐specific psychopathology. As argued elsewhere (Halbeisen, Braks, et al., 2022), men may show pronounced weight reductions due to higher levels of energy expenditure (Redman et al., 2014), but increased weight reductions could also reflect differences in therapy adherence between men and women. Given the paucity of studies on gender differences in EDs, especially for treatment outcomes in BED, further substantiation of these observations and their long‐term consequences is needed.…”
Section: Discussionmentioning
confidence: 78%
“…Thus far, the reasons for pronounced weight reductions with simultaneous parity in psychopathology outcomes remain elusive, as we cannot exclude that established assessments (like the EDE-Q) may be less sensitive towards capturing menspecific psychopathology. As argued elsewhere (Halbeisen, Braks, et al, 2022), men may show pronounced weight reductions due to higher levels of energy expenditure (Redman et al, 2014), but increased weight reductions could also reflect differences in therapy F I G U R E 1 Participants' percent weight loss trajectories across 50 days of treatment, as a function of gender and diagnostic group. Curved regression lines (with 95% confidence bands) were fitted using function geom_smooth(), method ('gam'), as implemented in R package ggplot2 Version 3.3.5 (Wickham, 2016).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Historically, men and boys have been overlooked in most approaches to eating disorders in socio-cultural and medical discourses. The focus has predominantly been on women and girls and on Anorexia and Bulimia Nervosa (Andersen, 1990; Wiseman et al, 1992; Weltzin et al, 2005; Greenberg & Schoen, 2008; Halbeisen et al, 2022a). This gender-biased narrative surrounding eating disorders is starting to change, most notably the adjustments made to the DSM-5 criteria to remove amenorrhea as a gendered criteria (Dakanalis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has found that the core features, such as drive for thinness, impulse regulation, and body dissatisfaction remain similar across both genders (Fernandez-Aranda et al, 2004; Hay et al, 2005; Fairburn, 2008; Bunnell, 2010; Nunez-Navarro et al, 2012). Similarly, research has shown that treatment modalities are equally valid when tested with men and boys (Halbeisen et al, 2022a; Woodside & Kaplan, 1994; Fairburn et al, 2008; Dakanalis et al, 2014) and that being a man is not a predictor for poor treatment outcomes (Fairburn, 2008). As a result, there is an emerging field of literature exploring men’s experience of eating disorders (Robinson et al, 2012; Räisänen & Hunt, 2014; Griffiths et al, 2015).…”
Section: Introductionmentioning
confidence: 99%